Desenvolvimento de processos químicos seguindo os princípios adotados pela química verde: redução e conversão de CO2 usando compostos de Mn(I) - Casale, Mariana Romano Camilo (2014)
Due to its versatile chemistry and ability to stabilize metals with low oxidation states, carbonyl compounds of transition metals play an important role in various fields of organometallic chemistry. In our research group, we have studied carbonyl compounds of manganese (I) over time and investigated their photochemical and spectroscopic properties. We carried out studies in photochemistry, electrochemistry (cyclic voltammetry and spectroelectrochemistry accompanied by UV-Vis and IR) and photoinduced intermolecular electron transfer (ET) reactions (with the electron acceptor MV2+, methylviologen) for the compound fac- [Mn(phen)(CO)3(4MeImH)](SO3CF3) (fac-1) where phen = 1,10-phenanthroline, 4MeImH = 4-methyl-imidazol and SO3CF3 = triflate ion, compound already synthesized and processed by the group. fac-1 shows electronic absorption bands in the UV-Vis at 380 (MLCT) and 270 nm (LLCT) in CH3CN and intense bands in IR between 2200 and 1800 cm-1, consistent with the facial arrangement of the three CO ligands in the sphere of coordination of the metal. The complex is stable in solid state and is a mixture of two isomers while in solution, the adjacent (A) and remote (R) isomers relative to the nitrogen atom (N) of the 4MeImH ligand which coordinates to the metal Mn. Encouraged by the results obtained by the group before, in which the compound fac-1 under irradiation of light in aqueous solution and in the absence of oxidizing agents in the reaction medium was able to cleave a molecule of water to produce molecular oxygen (O2) detected by a Clark electrode, we investigated the reduction and conversion of carbon dioxide molecules (CO2) to CO using this compound of Mn in organic solution, by photochemical and electrochemical means in N2 and CO2 atmosphere. Through the development of chemical processes, the petrochemical industry has made great contributions to mankind but at the same time the release of large amounts of CO2 in the atmosphere has harmed the environment. Capturing this gas emitted into the atmosphere primarily by the burning fossil fuels is a necessary strategy to minimize the greenhouse effect. In our photochemical studies, the complex was able to reduce CO2 to CO, product detected by 13C NMR (185 ppm), and the mechanisms of photochemical and electrochemical reactions of fac-1 in the presence of CO2 were checked. We carried out DFT calculations to corroborate experimental data and the results show the agreement of the UV-Vis and IR spectrum for the proposed product. A comparison of results shows the importance of ligand 4MeImH in the multiple photoinduced electron transfer reactions assisted by protons and the great potential of the fac-1 compound to participate in photocatalytic processes of interest, such as the reduction and conversion of CO2 to products of interest to the chemical industry.